Efikasi Diri Mahasiswa Perpustakaan dan Ilmu Informasi dalam Pencarian Informasi di UPT Perpustakaan Universitas Negeri Padang - Lailatul Rahmi; Marlini Marlini (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The purpose of this study is to describe students' self-efficacy in information searching at the Library and Information Science Department of UPT Library, Universitas Negeri Padang. This research employs a quantitative approach with a descriptive method, involving 116 PII students from the 2022 cohort at UNP as the population and sample, selected through random sampling. Data was collected through questionnaires. The results show that for the first indicator, personal self-evaluation, the average score is 3.88 (77.8%). For the second indicator, comparisons with others, the average score is 3.42 (68.5%). For the third indicator, physiological state, the average score is 3.79 (74.7%). For the fourth indicator, social feedback, the average score is 3.44 (69%), all indicating a high level of self-efficacy.